An analysis of financial literacy level of households of Punjab and Haryana state. (9th November 2021) - Purohit, Harsh; Chutani, Ravisha
The purpose of this paper is to assess the financial literacy level of households in the state of Punjab and Haryana. Also, it examines the relationship between financial literacy level and demographic variables. A modified questionnaire has been developed for data collection which covers the respondents' demographic variables and also identifies 33 variables affecting their financial literacy level. To frame the financial literacy level of the respondents, the median percentage of the responses of the sample was considered. A simple random sample of 800 respondents is used: male respondents, people in the age group of 31 to 35 years, above 35 years, married, graduates, post-graduates and doctorates, people living in semi-urban and urban areas, private employees, business persons and government employees, people having monthly income between Rs. 25, 000 to Rs. 45, 000 and >Rs. 45, 000 possess higher levels of financial literacy.